Development of a pressure acquisition system for detecting mandibular movements in ruminants - Geraldo Loyola Baiôco; Fábio Luiz Bertotti; André Luis Finkler da Silveira; João Ari Gualberto Hill (The Journal of Engineering and Exact Sciences)
Livestock farming is responsible for producing much of the animal protein that humans consume. Estimates of significant growth in the world population over the years highlight a demand not only for the expansion of animal production but also for an increase in livestock efficiency. To achieve this, one of the essential factors is improving the nutrition process, with the analysis of the ingestive behavior of ruminants being essential. Therefore, this work presents the development of a system for acquiring, storing, and transmitting signals from a pressure sensor for monitoring and evaluating masticatory movements in ruminants. This system employs a pressure sensor to obtain signals relating to chewing movement. A microcontroller acquires these signals at a sampling frequency of 100 Hz, and the resulting data are transmitted to a smartphone via Bluetooth and stored in a memory card for later analysis. Preliminary bench tests were carried out with the system installed on a full-size prototyped bovine head. Compression movements were applied to a silicone tube, causing pressure variations in the sensor. By transmitting the data to a smartphone via Bluetooth, it was possible to check the signal, adjust the gain of the instrumentation amplifier, and achieve the best positioning of the silicone tube in the mouthpiece. By reading the data recorded on a memory card, it was possible to obtain the signal profile, graphically demonstrating that the signal corresponds to the typical profile for this type of sensor.